Cost‐effectiveness of topical imiquimod and fluorouracil vs. photodynamic therapy for treatment of superficial basal‐cell carcinoma. (1st December 2014) - Arits, A.H.M.M.; Spoorenberg, E.; Mosterd, K.; Nelemans, P.; Kelleners‐Smeets, N.W.J.; Essers, B.A.B.
Summary: Background: A recent noninferiority randomized trial showed that in terms of clinical effectiveness imiquimod was superior and topical fluorouracil noninferior to methylaminolaevulinate photodynamic therapy (MAL‐PDT) for treatment of superficial basal‐cell carcinoma (sBCC). Although it was expected that MAL‐PDT would be more costly than either cream, a full cost‐effectiveness analysis is necessary to determine the balance between effectiveness and costs. Objective: To determine whether imiquimod or topical fluorouracil are cost‐effective treatments for sBCC compared with MAL‐PDT. Methods: An economic evaluation was performed from a healthcare perspective. Data on resource use and costs were collected alongside the randomized clinical trial. The incremental cost‐effectiveness ratio was expressed as the incremental costs per additional patient free of tumour recurrence. Results: At 12 months follow‐up, the total mean costs for MAL‐PDT were €680, for imiquimod cream €526 and for topical fluorouracil cream €388. Both imiquimod and topical fluorouracil were cost‐effective treatments compared with MAL‐PDT. Comparing costs and effectiveness of both creams led to a incremental investment of €4451 to achieve an additional patient free of tumour recurrence. The acceptability curve showed that, for a threshold value of €4451, the probability of imiquimod being more cost‐effective than topical fluorouracil was 50%. Conclusion: Based on the 12 months follow‐up results, imiquimod and topical fluorouracil cream are more cost‐effective than MAL‐PDT for treatment of sBCC. Hence, substituting MAL‐PDT with either imiquimod or topical fluorouracil results in cost savings; these savings will be larger for topical fluorouracil. Long‐term follow‐up effectiveness data are necessary to confirm the cost‐effectiveness of imiquimod vs. topical 5‐fluorouracil cream.